Using flipped classroom and peer instruction methodologies to improve introductory computer programming courses - Ruiz de Miras, Juan; Balsas‐Almagro, José R.; García‐Fernández, Ángel L. (Computer applications in engineering education, 2022)
Learning to write computer programs and engaging students in introductory programming subjects are difficult tasks. This study presents the results obtained when using flipped classroom and peer instruction methodologies in an introductory course of programming. Before the lecture, out‐of‐class study and on‐line homework questionnaires were applied, and peer instruction was used in the classroom to encourage students' participation and discussion, assisted by an on‐the‐fly assessment app. The main academic results, the degree of involvement in the course activities, and the students' feedback were collected and compared with similar data from previous academic years. Significantly better pass (χ2 = 12.94, p < .001) and dropout rates (χ2 = 7.08, p < .01) were obtained when using flipped classroom and peer instruction. Laboratory attendance also improved significantly (χ2 = 27.62, p < .001). Our results showed significant positive correlations between the work performed at home and the grade obtained in the final exam (ρ = 0.51, p < .001). According to the students' opinions, class preparation at home increased significantly (χ2 = 46.59, p < .001) by 33% due to the new methodologies used. These results, based on a sample of six offerings of the same programming course, suggest that the application of flipped classroom and peer instruction improves the quality of the autonomous work of the students as well as their involvement in the lectures, and therefore, their knowledge acquisition improves.